Effect of Dividend Policy, Funding Decision, Profitability towards Company Value - Sartika Ekadamayanti Soenarto, Avila; Susanti, Neneng (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to analyse and explain: (1) The effect of dividend policy; (2) influence of funding decisions; and (3) effect of profitability. The population of this research is a company in the manufacturing of textile and garment sub-sectors listed on the Indonesia Stock Exchange (IDX) period 2014 to 2018, with total samples of 6 companies. Data analysis results proved that (1) the value of the company does not affect the dividend policy, (2) the influence of the funding decision affects the company’s value, and (3) the influence of profitability affects the value of the company.